Meningkatkan Kreativitas Anak Usia Dini Dalam Menerapkan Seni Origami Di Taman Kanak-Knaak Tunas Inti Dusun Tebo Jaya - Andriani, Andriani; Ernawati, Andi; Sumiati, Cucum; Setiawati, Cahyani; Sudarya, Agus (Jurnal Pendidikan Indonesia, 2022)
The use of learning media is also very necessary, one of which is the art of paper folding. The art of paper folding is one of the things that inspires or makes children feel happy and excited to learn. creativity is very important to be developed because creativity can improve children's academic achievement. This study wanted to find out how the steps of the problem and the efforts made by the teacher in increasing the creativity of early childhood in applying the art of origami. The research is a research design using a descriptive approach. the population of this study were all teachers at Tunas Inti Kindergarten. while the sample in this study were informants totaling 2 people as foll Principals and Teachers. the instruments and methods of collecting data that the authors use in this study are observation, interviews and documentation. data analysis in the form of data reduction, presentation and drawing conclusions/verification. The research shows that in increasing the creativity of early childhood in the application of the art of origami. the discussion in the research is in the form of steps in the application of origami art such as folding into a triangular shape, the final stage of the lily flower, the paper has been finished. As for the problems faced by the teacher increasing the creativity of early childhood in applying the art of origami, namely the lack of motivation for children to learn the art of paper folding and there are still children who cannot do the art of paper folding. The efforts made by the teacher include creating comfortable learning room conditions and increasing motivation for early childhood and encouraging early childhood creativity, In the study that there was creativity in early childhood in the application of origami art in Tunas Inti Kindergarten before this paper folding activity was carried out by the teacher at Tunas Inti Kindergarten